Investigating ‘Relevancy’ of the Traditional Principle of the Right of Appropriation of Open Space and Fina’ in Contemporary Urban Poor Communities in Cairo, Egypt - Ahmed, Khaled Galal (Journal of Architecture and Urbanism, 2015)
Many scholars have questioned ‘relevancy’ of the principles of traditional urbanism where contradictory discourses have accumulated over time especially during the past few decades but unfortunately without a reliving answer. This research is a humble attempt to question this relevancy in our modern time in the domain of urban poor communities in Cairo through investigation one of the essential traditional housing principles, namely, “the right of appropriation of open spaces and fina’”. A method of qualitative/quantitative work has been embraced in which first, the investigated principle was defined from various sources of literature, then, field investigations through multiple case studies were conducted to address the question of relevancy to the urban poor communities today. It has been found that the principle is relevant to the residents’ practices and significantly relevant to their attitudes. This opens the door for what might be considered as (re) legitimization of the principle, after considering its probable health and environmental impacts, through integrating it within the current social housing processes in Cairo and in Egypt as a whole.